Biomarkers of platelet activation in acute coronary syndromes - Ferroni, Patrizia; Riondino, Silvia; Vazzana, Natale; Santoro, Nicole; Guadagni, Fiorella; Davì, Giovanni (Thrombosis and Haemostasis, 2012)
The most convincing evidence for the participation of platelets in arterial thrombosis in humans comes from studies of platelet activation in patients with acute coronary syndromes (ACS) and from trials of antiplatelet drugs. Both strongly support the concept that repeated episodes of platelet activation over the thrombogenic surface of a vulnerable plaque may contribute to the risk of death from coronary causes. However, the relation of in vivoplatelet activation and adverse clinical events to results of platelet function tests remains largely unknown. A valuable marker of in vivoplatelet activation should be specific, unaltered by pre-analytical artefacts and reproducibly measured by easily performed methods. This article describes current biomarkers of platelet activation in ACS, reviews their advantages and disadvantages, discusses their potential pitfalls, and demonstrates emerging data supporting the positive clinical implications of monitoring in vivo platelet ac- tivation in the setting of ACS.
Keywords: Acute coronary syndromes; platelet-derived biomarkers; thromboxane; metabolites; P-selectin; CD40L